EXAMINING THE INTERLINKAGES BETWEEN REGIONAL INFRASTRUCTURE DISPARITIES, ECONOMIC GROWTH, AND POVERTY: A CASE OF INDIAN STATES - Chotia, Varun; Muralidhar Rao, NV (Economic Annals, 2015)
This paper investigates the interlinkages between regional infrastructure disparities, economic growth, and poverty in the 21 major Indian States. An overall comprehensive index of infrastructure, the Composite Infrastructure Index (CII), is calculated for each Indian state using the Principal Component Analysis technique. In order to analyse the regional disparities between states in terms of infrastructure, they are ranked based on the calculated CII. We extend our analysis by evaluating the inter-relationship between the Composite Infrastructure Index, Per Capita Net State Domestic Product (PCNSDP), and poverty. The empirical analysis also proves that composite infrastructural growth and economic growth go hand in hand.